Hamnet [videorecording (DVD)] - Richter, Max (Universal Studios, 2026)
"William Shakespeare falls for the free-spirited Agnes. Their whirlwind romance leads to marriage and three children, but as Will's theatrical ambitions draw him to London, Agnes remains behind to manage the household. When tragedy strikes, their bond is deeply tested--but through grief and resilience, their journey inspires the creation of Shakespeare's timeless masterpiece, Hamlet."--